Sinulaflexiolide P, a cembrane-type diterpenoid from the Bornean soft coral Sinularia flexibilis - Phan, Chin-Soon; Yee, Chun-Sieng; Charles Santhanaraju Vairappan; Takahiro Ishii; Takashi Kamada (2019)
A bioassay-guided fractionation and chemical examination of the soft coral Sinularia flexibilis resulted in the isolation and characterization of sinulaflexiolides A−K (1−11), along with sinulariolone (12), 5-dehydrosinularolide (13), capillolide (14), sinulariolide (15), 5,8-epoxy-9-acetoxysinulariolide (16), flexibilide (17), dihydroflexibilide (18), and the enantiomer of 14-deoxycrassin (19). Their structures were determined on the basis of extensive spectroscopic (IR, MS, 2D NMR) data analysis and by comparison with spectroscopic data reported in the literature. Sinulaflexiolides D and E showed selective inhibitory activity against the gastric gland carcinoma cell line BGC-823 at 8.5 and 0.12 μM, respectively.